2013
DOI: 10.1016/j.socscimed.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The promises and perils of hospital autonomy

Abstract: This article investigates impacts of hospital autonomization in Viet Nam employing a "decision-space" framework that examines how hospitals have used their increased discretion and to what effect. Analysis suggests autonomization is associated with increased revenue, increasing staff pay, and greater investment in infrastructure and equipment. But autonomization is also associated with more costly and intensive treatment methods of uncertain contribution to the Vietnamese government's stated goal of quality he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…Here, the greater authority of the hospital manager under corporatisation allows them to innovate, but only if this is accompanied by higher capacities. Similar evidence appears in a study of hospital autonomy in Vietnam (London, 2013), which revealed that the increased revenue obtained by autonomised hospitals was not merely due to higher hospital charges but more to innovations introduced by the managers (such as generating patient-requested services and using equipment procured through joint ventures). The lack of improvement in efficiency of the corporatised hospitals in this study implies that the managers in these hospitals may not be exercising their higher decision space to innovate and to manage the hospital efficiently.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Here, the greater authority of the hospital manager under corporatisation allows them to innovate, but only if this is accompanied by higher capacities. Similar evidence appears in a study of hospital autonomy in Vietnam (London, 2013), which revealed that the increased revenue obtained by autonomised hospitals was not merely due to higher hospital charges but more to innovations introduced by the managers (such as generating patient-requested services and using equipment procured through joint ventures). The lack of improvement in efficiency of the corporatised hospitals in this study implies that the managers in these hospitals may not be exercising their higher decision space to innovate and to manage the hospital efficiently.…”
Section: Discussionsupporting
confidence: 73%
“…Vietnam (London, 2013). A monitoring system should also be considered in Indonesia as public hospitals here are the main provider of secondary care under the recently launched social security system promises universal health coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The decision space approach has been applied to case studies in Pakistan, 6,9 Bolivia, 8 Chile, 8 India, 8,26 the Phillipines, 8 Uganda, 8 Fiji, 11 Ghana, 10,12,27 South Africa, 28 Vietnam, 29 and Tanzania. 30 …”
Section: Resultsmentioning
confidence: 99%
“…Having the support of the organization better enables decision space, which in turn can be used to implement the organizational objectives. 14,21,29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation